Kolaborasi Sosial Mahasiswa dan UMKM : Berbagi Roti Coklat sebagai Wujud Kepedulian Sosial di Panti Asuhan - Nurul Hidayat; Alifah Syaputri; Putri Salsabila Zahra. M; Satri Lapu’; Kristina Sari; Ridwan Ridwan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Community Service Activities are a real form of students' social concern for the surrounding environment. Five students of the Management Study Program at Borneo Tarakan University carried out community service in collaboration with local MSME actors through an activity entitled